Sosialisasi Prosedur Konversi Pengelolaan Badan Usaha Milik Desa Menuju Sistem Syariah Di Kecamatan Tambang Kabupaten Kampar - Jenita; Rozi Andrini; Hamdalah; Hertina (Jurnal Pengabdian Masyarakat Akademisi, 2022)
BUMDes is a village economic institution/agency formed and owned by the village government and the community. The existence of BUMDes is essential to encourage the economy of rural communities. Tambang District, Kampar Regency has 17 BUMDes which play a role in improving the economy of its people. However, the BUMDes are still managed using a conventional system. The description of the desire to convert to a sharia BUMDes system has existed for a long time. However, the BUMDes in Tambang District still does not have a technical picture of the conversion to Sharia BUMDes management, so socialization is needed. The purpose of this service is to provide understanding for BUMDes BUMDes managers regarding the conversion procedure for BUMDes management with a sharia system and provide motivation for BUMDes management to convert BUMDes management to a sharia system, with material on conversion procedures, sharia BUMDes management, sharia BUMDes management principles. The results increase understanding of the conversion procedure to sharia BUMDes among BUMDes managers in the Mining sub-district. This can be seen from the statements and enthusiasm of the participants in the implementation of service from the beginning to the end of the activity. The importance of this service activity is because it shows that after getting an explanation from the service team and the motivation provided, it shows an increase in understanding of the conversion